Investigation of the inhibitory effects of human carbonic anhydrase i and jack bean urease by coumarin derivates - OGAN, AYŞE; DANIŞ, ÖZKAN (Bentham Science Publishers B.V., 2018)
Introduction: This study investigated the in vitro inhibition properties of newly synthesized coumarin derivates (C1-C5) against human carbonic anhdyrase I (hCA-I) and jack bean urease. Activities were expressed as IC50 (mg/mL), the concentration reducing 50% of the enzymes. The IC50 values for hCA-I ranged 5.20 µM from 12.10 µM, with compound C3 exhibiting the highest activity. The inhibition values for urease ranged 22.30 µM to 39.00 µM, the highest activity being observed in C5. Conclusion: Comparing the inhibitions with standard inhibitors of the enzymes, while the samples exhibited moderate inhibitions against hCA I, high inhibition was determined against urease. © 2018 Bentham Science Publishers.
Keywords: Carbonic anhydrase; Coumarin; Inhibition; Jack bean; Synthesis compounds; Urease